Synthesis of mussel-inspired polydopamine-gallium nanoparticles for biomedical applications - Teixeira, Jean Valdir Uchôa [UNESP]; Maia, Fátima Raquel Azevedo; Carvalho, Mariana; Reis, Rui; Oliveira, Joaquim Miguel; Lisboa-Filho, Paulo Noronha [UNESP]; Claro, Ana Paula Rosifni Alves [UNESP] (Taylor & Francis, 2021)
Aim: To established a simple, controlled and reproducible method to synthesize gallium (Ga)-coated polydopamine (PDA) nanoparticles (NPs). Materials & methods: PDA NPs were synthesized in alkali medium with posterior Ga shell formation due to ion chelation on the NP surface. Results: The obtained results with energy-dispersive X-ray spectroscopy confirmed the incorporation of Ga on the PDA NP surface. The cytotoxicity of Ga-coated PDA NPs was evaluated in vitro at different concentrations in contact with human adipose-derived stem cells. Further cell analysis also demonstrated the benefit of Ga-coated PDA NPs, which increased the cell proliferation rate compared with noncoated PDA NPs. Conclusion: This study indicated that Ga could work as an appropriate shell for PDA NPs, inducing cell proliferation at the analyzed concentrations.
Keywords: core/shell; cytotoxicity; gallium incorporation; nanoparticle synthesis